Exploring the experiences of international students living in Malaysia - Dawood Abdulmalek Yahya Al-Hidabi, Dawood; Thartori, Voltisa; Abdullah, Mohamad Ridhuan; Sahrir, Muhammad Sabri; Alzabid, Talal Saeed Omar; Shakafa, Mahoud (Human Resource Management Academic Research Society, 2023)
Retaining international students has been a significant concern for higher education institutions globally. This qualitative study aimed to explore the experiences of eight students from conflict zones who are studying at an International University in Malaysia.The objectives of this research paper are as follows: (i)To what extent faculty use effective teaching? (ii)To what extent does a university provide effective and efficient administration? (iii) What are the psychological and health care services offered by the university? (iv) To what extent dominant university culture and environment are Islamic? This study employed a qualitative study design using in-depth semi-structured interviews. The findings indicate that during the COVID19 lockdown, students lacked guidance and mentorship, and the support services provided by the university were not effective. While students perceived that the faculty represented Islamic values, some academic staff lacked competency, and some administrative staff had low employee efficiency, leading to a perception that they do not represent Islamic values. Keywords: Student Retention, Qualitative Study, Conflict War-Zone Countries.